Family Sibling Effect and Executives’ Corporate Social Behavior - Zheng, Minna; Ren, Guangqian; Zhuang, Lingling (Frontiers in Psychology, 2021)
Corporate social responsibility is an important business strategy for enterprises. Scholars have conducted much beneficial research on the relationship of executives’ recognitive traits and firms’ CSR behavior, but rarely focus on the impact of executives’ early recognitive traits derived from family sibling interaction. This paper takes Chinese A-shared private listed companies from 2014 to 2017 as the research samples to investigate the effect of the number of executives’ siblings on the early family sibling and corporate social responsibility behavior. We further study the moderating effect of birth order and gender composition in siblings on this relationship. The results show that there is an inversed U-shaped relationship between the number of executives’ siblings and corporate social responsibility behavior. Further research shows that the relationship between the number of executives’ siblings and CSR behavior is strengthened when an executive is first-born or has female sibling(s).